A New Combination Method of N-doped TiO2 Nanoparticles Synthesis for Heavy Metal Ions Cr(VI) Photoreduction Applications - Diana Vanda Wellia; M. Rafli Habibillah; Atika Syafawi; Rizka Rahmadini; Rahmayeni Rahmayeni; Nurul Pratiwi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Through a combination of biosynthetic and hydrothermal methods, N-doped TiO2 photocatalyst has been successfully synthesized using various concentrations of ammonia as a nitrogen source, namely 10% w/w (NTO10), 20% w/w (NTO20), 35% w/w (NTO35), and 50% w/w (NTO50). The synthesis of TiO2 was conducted using Aloe vera (L) Burm F. rind extract as a natural capping agent via the biosynthetic method, followed by a nitrogen doping process via the hydrothermal method. The X-ray Diffraction (XRD) analysis revealed that all phases were anatase. According to the results of the UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS) analysis using the Tauc-Plot method, all N-doped TiO2 samples showed a decrease in the energy gap compared to the TO sample. This indicates that the doping of TiO2 using nitrogen has been successfully doped into TiO2. The photocatalytic activity of N-doped TiO2 was evaluated for the photoreduction of the Cr(VI) model pollutant using a 24-watt LED lamp as a visible light source for 120 minutes. The results indicate that the NTO35 is the best-prepared N-doped TiO2, which showed a reduced rate for the Cr (VI) model pollutant of 50.88%, or two times greater than that of undoped TiO2.